Self-respect and independence of mind : the challenge of Fukuzawa Yukichi - Kitaoka, Shin'ichi, 1948-; Vardaman, James M., 1947- (Chiyoda-ku, Tokyo : Japan Publishing Industry Foundation for Cult ure, 2017)
"It is said that Japan is currently experiencing its third opening t o the outside world. However, in terms of importance, rather than the s o-called second opening--which refers to the reforms following World Wa r II--the more significant opening was that of the Meiji Restoration, i nitiated and carried out by the Japanese themselves. Consequently, as J apan today finds itself feeling trapped with a sense of despair, it is to the Meiji era that we should turn, and more than to anyone else, the person we should turn to is Fukuzawa Yukichi. With the general reader in mind, this volume brings together the results of the present-day res earch into the accomplishments of Fukuzawa as part of an overall apprai sal of the man himself"--Back cover.
The Nakatsu period -- Ogata's Tekijuku -- Going to America -- Learni ng about Europe -- Condition in the West -- Keio Gijuku -- An encourage ment of learning -- An outline of a theory of civilization -- Leaders o f Meiji restoration and Fukuzawa Yukichi -- "Discourse on the National Assembly" and the political crisis of 1881 -- Home and daily life -- Th e Korean issue -- Establishment of the cabinet system and treaty revisi on -- The early diet and the Sino-Japanese War -- Last years and death -- Fukuzawa chronology.
Translation from Japanese of: Dokuritsu jison : Fukuzawa Yukichi no chåosen
Text translated into English from Japanese.
Includes bibliographical references (p. 322-324).
Keywords: Fukuzawa, Yukichi -- (1835-1901).; Educators -- Japan -- Biography